Desafíos alimentarios para un mundo que envejece - Fanny Petermann-Rocha; Claudia Troncoso-Pantoja; Amparo Gamero; Patricio Pérez-Armijo; Elena Carrillo-Alvarez; Rodrigo Daga; Manuel Reig García-Galbis; Alberto Pérez-López; Néstor Benítez Brito; Tania Fernández-Villa; Diego A. Bonilla; Macarena Lozano-Lorca; et al. (Revista Española de Nutrición Humana y Dietética, 2023)
N/A